Marriage Readiness Cards and Adolescent Knowledge: Addressing Child Marriage - Sakti, Putri Mulia; Ramadhan, Kadar; Faisal, T. Iskandar (Jurnal Bidan Cerdas, 2023)
Introduction: Child marriage is a concerning issue associated with various health and social problems, including stress, suicide, despair, low self-esteem, family and social difficulties, limited job choices, financial dependence, and school dropout. Objectives: This study determined the relationship between marriage readiness cards and the improvement of adolescent knowledge in unraveling child marriages. Methods: The research utilized a cross-sectional design conducted at the adolescent health post within the Pantoloan Community Health Center's working area in July 2023. Purposive sampling involved 36 respondents, and data collection utilized a 10-question questionnaire. Univariate and bivariate analyses (Wilcoxon) were applied to the collected data, presented through tables and narrative descriptions. Results: The research findings indicated a significant improvement in adolescent knowledge after the intervention, as evidenced by a negative rank of 0 and a positive rank of 5, with a statistically significant p-value of 0.000. In conclusion, engaging educational media, such as marriage readiness cards, proved effective in enhancing respondents' knowledge. This study recommends community health centers to adopt educational media that capture adolescents' attention for more impactful health promotion initiatives.